Cardiomyocyte regeneration: A consensus statement - Eschenhagen, T; Bolli, R; Braun, T; Field, LJ; Fleischmann, BK; Frisén, J; Giacca, M; Hare, JM; Houser, S; Lee, RT; Marbán, E; Martin, JF; et al. (American Heart Association, 2017)
Cell therapy is an exciting option for repairing the injured heart, one that has attracted considerable interest over the past 15 years. Consensus exists that the injection/infusion or tissue-based implantation of various cell types may exert therapeutic effects, and there is general agreement that additional molecular, translational, and clinical studies are required to define the optimal cell source, method of delivery, and underlying mechanism(s) of action. One of the remaining questions in this field pertains to cardiomyocyte turnover under normal and diseased conditions and its contribution to the beneficial effects of cell therapy. Although results published in the literature have not been consistent, we believe that the time is ripe to formulate a consensus for many of the pertinent questions. It is important to emphasize that the focus of this consensus statement is on cardiomyocyte renewal; it is not on cell therapy in general. Although we touch on some aspects of therapeutic strategies based on delivery of exogenous cells, our intent here is to define areas of agreement and areas requiring further elucidation related to the regenerative potential of the myocardium itself. We have included references to the scientific literature throughout the document. Although it is impossible for us to include all publications in this expansive field, representative studies that corroborate statements herein have been cited.